The Relationship Between Dependency and Sport Participation, Category of Sport, and Gender in College Athletics - Toye, Peter J.; Lanning, Wayne (My University, 1989)
This study investigated the relationship between the personality trait of dependency, including the related construct of locus of control, and sport participation of male and female athletes. The student athletes consisted of 68 females and 95 males from both team and individual sports. Data were collected by means of the dependency scores on the Personality Factory Questionnaire (16PF) and Rotter's Locus of Control instrument. The total sample of athletes was not found to be different from non athletes in dependency, but male athletes were less dependent than male non athletes. Female basketball athletes were more dependent than female volleyball athletes. In addition, athletes were significantly more external on locus of control than non athletes. No meaningful relationship was found between dependency and locus of control. The data revealed from this study suggested that the athletic population is essentially no different from the non athlete population on dependency.
Keywords: skills; non-athlete students